Strategi Guru Mengelola Kelas untuk Meningkatkan Disiplin dan Motivasi Belajar Siswa di Sekolah Dasar - Novi Nurdian; Muhammad Supian Sauri; Armin Fani (DIDAKTIKA, 2025)
"Effective classroom management is the key to creating a conducive learning environment, improving discipline, and motivating students to learn. Teachers play an important role in implementing classroom management strategies that can direct students' behavior in a positive direction. The application of the right classroom management strategies is expected to improve student discipline and learning motivation in schools. This study aims to analyze the classroom management strategies used by teachers to improve student discipline and their implications for learning motivation in elementary schools. This research uses a qualitative approach with a case study design, conducted at an elementary school in Banjarmasin City. The subjects of the study are the class teacher and students, with data collected through observation, semi-structured interviews, and documentation. The results show that the teacher applies several key strategies, including consistent enforcement of classroom rules, providing positive reinforcement, and a personal approach in handling discipline violations. These strategies not only improve student discipline but also motivate them by creating a conducive learning environment, fostering positive relationships between teachers and students, and rewarding student efforts. These findings support relevant classroom management and learning motivation theories.